Analysis of Sexual Orientation in Adolescents at Junior High School Jakarta - Putri Azzahroh; Vivi Silawati; Aginta Haryuni Putri (Rajaki of Tulip Medika Publisher, 2023)
Background: In adolescence, sexual urges will appear more easily, there is a possibility of choosing a non-heterosexual sexual orientation. To prevent this, it is necessary to be identified in early adolescence. Purpose: to determine the sexual orientation of adolescents at SMP 1 Barunawati Jakarta and to analyze the relationship between perceptions, attitudes, parenting styles, intensity of access to pornography, environment and trauma to sexual orientation using the Chi Square statistical test. Methods: This research is a descriptive study with a cross-sectional research design with a research instrument using a questionnaire. The population in this study were all students of class VII and VIII at SMP 1 Barunawati Jakarta with a total sample of 139 people. Results: Based on the results of univariate analysis, it was found that 67.6% of adolescents were heterosexual and 32.4% were at risk of non-heterosexuality. Meanwhile, the results of the bivariate analysis showed that the variables of perception, attitude and intensity of access to pornography had a significant relationship to sexual orientation with P values of 0.000, 0.009 and 0.003. Conclusions: Students at SMP 1 Barunawati Jakarta have a sexual orientation that is in accordance with societal norms. Perceptions, attitudes and intensity of access to pornography have a significant relationship to the formation of sexual orientation. It is hoped that midwives can detect changes in sexual orientation in adolescents from an early age so that they can be treated immediately.